Where Do Stars Come From? The Role of Star vs. Nonstar Collaborators in Creative Settings - Liu, Haibo; Mihm, Jürgen; Sosa, Manuel E. (Organization Science, 2018)
Creative stars make disproportionately influential contributions to their fields. Yet we know little about how an innovator’s creative performance is affected by collaborating with stars. This paper studies the creative aspects of interpersonal collaboration from a distinct perspective: the quality of the collaborator. Both star and nonstar collaborators provide different benefits to a focal innovator. The innovator benefits from collaborating with nonstars because they may provide access to diverse information improving the outcome of the creative task at hand. In contrast, the focal innovator benefits from collaborating with stars because the focal innovator can also experience and learn from the star’s superior set of creative synthesis skills (which integrate diverse, sometimes contradictory ideas into new coherent and holistic solutions) and, thus, build lasting creative capabilities. Building on theoretical arguments about those two different collaboration purposes, we first examine how a star collaboration (versus a nonstar collaboration) affects a comprehensive measure of an innovator’s creativity: the likelihood of emerging as a star. Second, we examine how the different creative benefits of engaging with a star versus a nonstar collaborator affect the effect of two widely studied aspects of interpersonal collaboration on star emergence: social network cohesion and expertise similarity. In contrast to collaborations with nonstars, for which social cohesion and expertise similarity limit access to diverse information, negatively affecting star emergence, social network cohesion and expertise similarity have a decidedly positive effect on star collaborations by improving the transfer of the star’s set of creative skills. Our empirical setting consists of designers who have been granted design patents in the United States from 1975 through 2010.